2023
DOI: 10.1021/acsomega.3c06856
|View full text |Cite
|
Sign up to set email alerts
|

Stacking Fault Formation in LiNi0.6Co0.2Mn0.2O2 during Cycling: Fundamental Insights into the Direct Recycling of Spent Lithium-Ion Batteries

Kazuhiko Mukai

Abstract: As the global marketplace for lithium-ion batteries (LIBs) proliferates, technologies for efficient and environmentally friendly recycling, i.e., direct recycling, of spent LIBs are urgently required. In this contribution, we elucidated the mechanisms underlying the degradation that occurs during the cycling of a Li/LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM622) cell. The results provided fundamental insights into the optimum procedures for direct recycling using a recently developed, state-of-the-art positive electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The decrease (increase) in a h ( c h ) resembles the change in a h ( c h ) upon the charge reaction. 18 As listed in Table 1, the ICP-AES analysis confirmed that the Li composition decreased as leaching proceeded. By contrast, the a h and c h values with H 2 O 2 were almost constant, regardless of the leaching time, suggesting that Li + ions are not effectively extracted from the NCM622 lattice.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The decrease (increase) in a h ( c h ) resembles the change in a h ( c h ) upon the charge reaction. 18 As listed in Table 1, the ICP-AES analysis confirmed that the Li composition decreased as leaching proceeded. By contrast, the a h and c h values with H 2 O 2 were almost constant, regardless of the leaching time, suggesting that Li + ions are not effectively extracted from the NCM622 lattice.…”
Section: Resultsmentioning
confidence: 77%
“…The structural and electrochemical properties of pristine NCM622 are similar to those previously reported for NCM622. 17,18…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Unfortunately, the traditional inorganic electrode materials (e.g., LiCoO 2 , LiFePO 4 , and LiNixMnyCo 1-x-y O 2 ) used for commercial LIBs rely heavily on the non-renewable metal resources and energy-intensive industries, endowing the existing LIBs unsustainable for the ever-increasing energy storage market. [4][5] As an alternative, organic electrode materials (OEMs) have emerged to tackle the bottlenecks facing inorganic materials due to their inherent merits of abundant resources, low cost, and structural diversity. [6][7][8] Recently, incredible breakthroughs regarding the electrochemical performances of OEMs have been achieved, in particular for their impressive capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid expansion of Li‐ion batteries (LIBs) in large‐scale energy storage systems calls for electrodes featuring cost‐efficiency and environmental friendliness [1–3] . Unfortunately, the traditional inorganic electrode materials (e.g., LiCoO 2 , LiFePO 4 , and LiNixMnyCo 1‐x‐y O 2 ) used for commercial LIBs rely heavily on the non‐renewable metal resources and energy‐intensive industries, endowing the existing LIBs unsustainable for the ever‐increasing energy storage market [4–5] . As an alternative, organic electrode materials (OEMs) have emerged to tackle the bottlenecks facing inorganic materials due to their inherent merits of abundant resources, low cost, and structural diversity [6–8] .…”
Section: Introductionmentioning
confidence: 99%